Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $p$ be an odd prime.How to prove that

$$1^{p-2}+2^{p-2}+\cdots+\left(\frac{p-1}{2}\right)^{p-2}\equiv\frac{2-2^p}{p}\pmod p.$$

share|improve this question
    
Let $f(x)=(x+1(\frac{p-1}{2}))(x+2(\frac{p-3}{2})...(x+(\frac{p-1}{2})(1))$,and $a=$ coefficient of $x$ of $f(x)$. Then the problem is equivalent to showing that $a\equiv 8(-1)^{\frac{p-1}{2}} (\frac{2^{p-1}-1}{p}) (mod p)$. I dunno if this would help us solve this problem. –  Ben Jun 30 '12 at 9:53
    
Am I being stupid or does this not make sense since $p$ is not invertible mod $p$? –  fretty Jun 30 '12 at 12:29
1  
$2-2^p$ is divisible by $p$,so here $\frac{2-2^p}{p}$ is an integer and $\frac{1}{p}$ does not mean the inverse in the field $\mathbb{Z}/p\mathbb{Z}$. –  Ben Jun 30 '12 at 12:30
    
Yes, I didn't look at the numerator in detail so I was being stupid. –  fretty Jun 30 '12 at 12:40
add comment

2 Answers

up vote 3 down vote accepted

I find that this identity is stated in this paper:

Lehmer, E. "On Congruences Involving Bernoulli Numbers and the Quotients of Fermat and Wilson." Ann. Math. 39, 350-360, 1938 : http://www.jstor.org/discover/10.2307/1968791?uid=2134&uid=2&uid=70&uid=4&sid=56284309973

Equation (30) in the paper answers your question.

EDIT:

In fact,we can use a simpler method to solve this problem.

Let $q(a)=\frac{a^{p-1}-1}{p}$ for all $a$ such that $\gcd(a,p)=1$. It is not difficult to show that $q(ab) \equiv q(a)+q(b) \pmod{p}...(1)$.

Let $a$ be an arbitrary integer which is relatively prime to $p$. For each $v \in \{1,2,...,p-1\}$,let $av=\lfloor{\frac{av}{p}} \rfloor p+r_v$. Then we can see that $r_v$,($r=1,2,...,p-1$) also runs over ${1,2,...,p-1}$. So $q(av)=((\lfloor{\frac{av}{p}} \rfloor p+r_v)^{p-1}-1)/p\equiv q(r_v)-\lfloor{\frac{av}{p}} \rfloor r_v^{p-2} \equiv q(r_v)-\frac{1}{av} \left \lfloor \frac{av}{p} \right \rfloor \pmod{p}$

So, $\sum_{v=1}^{p-1} q(av) \equiv \sum_{v=1}^{p-1} (q(r_v)-\frac{1}{av} \left \lfloor \frac{av}{p} \right \rfloor)\equiv \sum_{v=1}^{p-1} q(v)-\sum_{v=1}^{p-1}\frac{1}{av} \left \lfloor \frac{av}{p} \right \rfloor \pmod{p}...(2)$

Then by $(1),(2)$,we get $q(a) \equiv \sum_{v=1}^{p-1}\frac{1}{av} \left \lfloor \frac{av}{p} \right \rfloor \pmod{p}...(3) $

Take $a=2$, $\frac{2^p-2}{p} \equiv \sum_{v=1}^{p-1}\frac{1}{v} \left \lfloor \frac{2v}{p} \right \rfloor \equiv \sum_{p/2 <v} \frac{1}{v} \equiv -\sum_{v=1}^{(p-1)/2} \frac{1}{v} \equiv -\sum_{v=1}^{(p-1)/2} v^{p-2} \pmod{p}$

As a result,

$1^{p-2}+2^{p-2}+\cdots+\left(\frac{p-1}{2}\right)^{p-2}\equiv\frac{2-2^p}{p}\pmod p.$

share|improve this answer
2  
Freely available version. –  anon Jun 30 '12 at 12:45
1  
BenLi,could you look at this solution : store2.up-00.com/June12/RoL51753.jpg –  Frank Jul 2 '12 at 17:56
    
@MohammedAl-mubark, your solution looks alright. That's how I did it. Look below. –  DonAntonio Jul 3 '12 at 1:50
    
@Mohammed Al-mubark:your solution looks much simpler and more direct. –  Ben Jul 3 '12 at 2:00
add comment

$$2^p=(1+1)^p=\sum_{k=0}^p\binom {p}{k}=\left[\binom{p}{0}+\binom{p}{p}\right]+\ldots+\left[\binom{p}{\frac{p-1}{2}}+\binom{p}{\frac{p+1}{2}}\right]=$$ $$=2\left[\binom{p}{0}+\ldots+\binom{p}{\frac{p-1}{2}}\right]$$

and etc.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.